Isolation and screening of phosphorus solubilizing bacteria from saline alkali soil and their potential for Pb pollution remediation - Zhang, Chaonan; Chen, Haoming; Dai, Yao; Chen, Yan; Tian, Yuxin; Huo, Zongli (Frontiers in Bioengineering and Biotechnology, 2023)
The high pH and salinity of saline alkali soil not only seriously restrict the growth of crops, but also aggravate the pollution of heavy metals. The fixation of heavy metals and the regulation of pH by phosphorus solubilizing microorganisms may become a new way to improve and repair saline alkali soil. In this study, a salt and alkali tolerant strain (CZ-B1, CGMCC No.: 1.19458) was isolated from saline alkali soil, and it was be domesticated under salt/alkali/Pb stress. The strain was identified as Bacillus amyloliquefaciens by morphology and 16S rRNA gene sequence analysis. CZ-B1 has a wide temperature adaptation range, and maintains high activity at 25-45 ℃. The optimum growth temperature is about 35-40 ℃. The maximum salt stress and pH value that it can tolerance are 100 g/L and 9 respectively, and its tolerance to Pb2+ can reach 2000 mg/L. The phosphorus release amount of CZ-B1 to Ca3(PO4)2 within 72h is 91.00-102.73 mg/L. The phosphate solubilizing index in PVK agar medium and NBRIP agar medium are more than 2, which can be defined as phosphate solubilizing bacteria. Moreover, the dissolution of CZ-B1 to phosphorus is mainly attributed to tartaric acid, citric acid and succinic acid. In addition, the removal rate of Pb2+ by CZ-B1 can reach 90.38% for 500 mg/L. This study found that CZ-B1 can immobilize Pb through three biological mechanisms (organic acid, extracellular polymers and mineralization reaction). XRD and SEM confirmed that the release of succinic acid (10.97 g/L) and citric acid (5.26 g/L) may be the main mechanism for CZ-B1 to form phosphate and oxalate and resistance to Pb stress. In addition, the high enrichment of Pb2+ by EPS can increase the rate of extracellular electron transfer and accelerate the mineralization of CZ-B1. The screening and domestication of saline-tolerant phosphorus-solubilizing bacteria not only help to remediate Pb contamination in saline soils, but also can provide assistance to plant growth.